Implementasi Peraturan Daerah Nomor 08 Tahun 2015 tentang Penataan dan Pemberdayaan Pedagang Kaki Lima di Pasar Ceplak Kecamatan Sukamulya Kabupaten Tangerang - Aan Ansorullah (Epistemik Press, 2020)
This research explains the implementation of Regional Regulation No. 08 about structuring and empowerment of street vendors conducted by the Tangerang District Government, particularly in the Market Ceplak, District Sukamulya. The purpose of this study is to determine how the implementation of the Regional Regulation No. 08 Year 2015 About the Arrangement and Empowerment Street vendors (PKL), especially in District Sukamulya. The theory used in this research is Donald Van Metter and Carl Van Horn's policy implementation theory. In this theory, there are six variables that affect the performance of public policies, namely size and policy objectives, resources, characteristics of implementing agents, attitudes / tendencies of the implementers, communication between organizations. The research method used is descriptive qualitative research method. The results of this research indicate that the implementation of Regional Regulation Number 08 of 2015 concerning Structuring and Empowerment of Street Vendors in Tangerang Regency, especially in the Ceplak Market, Sukamulya District has not been carried out optimally, this can be seen in the presentation of data that PKL on the Ceplak market have not been well organized, trading activities are still carried out on the sidewalk . so in other words the relocation of Ceplak Market street vendors has not gone as expected.